Implementation of Permenaker No. 2 of 2015 From The Channeling Agency In Channeling Workers - Arsyad, Syaif; M. Hadi Subhan; Radian Salman (POLITICO, 2024)
This study aims to examine the Implementation of Permenaker No. 2 of 2015 From The Channeling Agency In Channeling Workers. Work as a domestic worker (DW) is an important source of livelihood for the lower middle class for women and men in developing countries such as Indonesia, because the work is carried out in the household and is considered informal work, there are no clear regulations governing it, as a result it is often not noticed and considered a very low job. Lembaga Penyalur Pekerja Rumah Tangga (LPPRT) is expected to be a bridge as well as a protector of domestic workers regulated in PERMENAKER RI No.2 of 2015. Starting from the initial recruitment process, then the selection process and up to job placement, during work, and after returning to the area of origin. The main problem faced by domestic workers, as well as the obstacles experienced in obtaining their rights, both men and women working as domestic workers, is legal certainty and clarity of their social status. This research focuses on the conflict of interest of the channeling agency when distributing domestic workers because the channeling agency that provides the service fee is the employer.